Modelling the role of acidic species on CO2 corrosion prediction - Mohamad Azwan, Mohd Ghazali (2013)
The presence of acetic acid (HAc) in formation water of oil and gas reservoirs has long been suspected to contribute to the CO2 corrosion rate. The prediction model has been developed based on mechanistic theories which is involved the fundamental of electrochemical reaction for partial cathodic and anodic process on the metal surface. By using this prediction model, the corrosion behaviour of carbon steel in the presenceof HAc in combination with pH and temperature at simultaneously has been investigated. The corrosion prediction model was verified by comparing calculated corrosion rates with the corrosion data obtained from various literature sources andcorrosion prediction software’s and it’s showed a good relationship in correlation and regression relationship and provided high precision in standard error estimation. From the findings, electrochemical measurements have shown that the presence of acetic acid affects predominantly the cathodic reaction and increased the rate of corrosion, which is agreed well with the general understanding of the CO2 corrosion process.